Adaptasi Praktik Pajak Pada Zakat Sebagai Alternatif Pengelolaan Zakat Secara Efektif - Fatih Fuadi (Falah: Jurnal Ekonomi Syariah, 2017)
Indonesia is a country that has diverse cultures and religions, so zakah and tax are two things that cannot be released. Both of them have different meanings and treatments, where zakah is only charged to Muslims and the tax are imposed on all Indonesian citizens whose income above an average. This paper aims to determine the similarities and differences of the concept of zakah and tax, the opinion of scholars about them, and the last is to know about the effective zakah management of with the adoption of some concept of tax management. In this study, used data collection techniques in the form of library research. The research findings show that the similarity between the concept of zakah and the tax is as follows; both of them have the element of coercion and management. The difference both of the are as follows; in terms of name, legal basis and nature of its obligations, as well as from the object, percentage, and utilization. The concept of tax which can be applied in order to obtain an effective zakah management are as follows: first, giving sanction to the zakah manager and negligence muzakki. Second, an improvement of zakah administration system consisting of function, system and institution. Third, the existence of zakah information system. Fourth, the formation of zakah directorate as well as the formation of tax directorate, And the latter developing an independent institution that acts as an auditor of zakah institution.